2011
DOI: 10.1177/1741143210390058
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Educational Reforms on the Work of the School Principal in the United Arab Emirates

Abstract: Although much has been written about the complexity of educational change and reform elsewhere, the educational reform movement in the United Arab Emirates (UAE) is a relatively recent phenomenon with little systematic documentation as yet; educators are still searching for a clear understanding of their roles. However, it is clear that the leadership of the country is exerting great pressure for reform in schools and there is a sense of urgency about the need for largescale change. This article examines the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…Two articles traced the implementation of a certain reform in schools and specifically its implications for educational leadership. Thorne (2011) used a case study approach in one elementary school in the UAE that has been selected to pilot a local reform according to which primary mathematics and science would be delivered by the use of the English language. Fatina, the principal, faced several sources of tension during the implementation of this reform.…”
Section: Theme 2: Reforms Changes and Educational Leadership And Manmentioning
confidence: 99%
“…Two articles traced the implementation of a certain reform in schools and specifically its implications for educational leadership. Thorne (2011) used a case study approach in one elementary school in the UAE that has been selected to pilot a local reform according to which primary mathematics and science would be delivered by the use of the English language. Fatina, the principal, faced several sources of tension during the implementation of this reform.…”
Section: Theme 2: Reforms Changes and Educational Leadership And Manmentioning
confidence: 99%
“…W. Fischer & Rose, 2001;K. W. Fischer & Rose, 1998;Helfenbein, 2012;Ravitch, 2010;Thorne, 2011). Such practices are indicative of false consciousness for students and parents, while being a misrepresentation of optimal learning as well (J.…”
Section: Motivation and Engagementmentioning
confidence: 99%
“…Suggestions for improvement include: greater centralization of decision-making by ADEC, intensive ongoing language and pedagogy PD for teachers and leaders, establishment of career pathways, and a greater focus on research as a part of the reform effort (Thorne, 2011 The Tamkeen project is the focus of Al Taneiji's qualitative phenomenological study of teacher perceptions regarding their experience in the professional development program. The seven Cycle 1 and 2 teachers interviewed reported that the PD content addressed their needs and the needs of the school, a variety of training formats were offered, and that they preferred the use of internal trainers (including school leadership) more than direct delivery from the PD provider.…”
Section: Purpose Of the Studymentioning
confidence: 99%